Surgical Outcomes, Complications, and Management Strategies for Foramen Magnum Meningiomas - Magill, Stephen T.; Shahin, Maryam N.; Lucas, Calixto-Hope G.; Yen, Adam J.; Lee, David S.; Raleigh, David R.; Aghi, Manish K.; Theodosopoulos, Philip V.; McDermott, Michael W. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Foramen magnum meningiomas (FMM) are complex lesions because of their proximity to the brain stem and posterior cerebrovasculature. The objective of this study is to report surgical outcomes and complications after resection of FMM.Methods A retrospective chart review was conducted on patients with FMM from 1998 to 2015. Univariate logistic regression and recursive partitioning analysis were used to identify risk factors associated with complications and extent of resection (EOR).Results We identified 28 patients with FMM. Median follow-up was 5.9 years. Tumors were World Health Organization grade I (92.9%) or grade II (7.1%). The vertebral artery was completely encased (25%), partially encased (11%), or not encased (64%). Median size was 11.9 cm3. EOR was gross total (39%) and subtotal (61%). The observed recurrence rate was 4% (n = 1). There were 38 complications in 12 patients (43%), and 6 patients (21%) had complications requiring additional surgery. Complications included cerebrospinal fluid leak/hydrocephalus (n = 7, 25%), weakness (n = 4, 14%), numbness (n = 4, 14%), and cranial nerve deficits: IX, X (n = 4, 14%), XI (n = 2, 7%), XII (n = 5, 18%). Medical complications included pneumonia (n = 1, 4%) and meningitis (n = 1, 4%). Tumor volume greater than 14 cm3 (odds ratio [OR] = 21.7, p = 0.0010), any vertebral artery encasement (OR 6.1, p = 0.0386), and subtotal resection (OR 6.4, p = 0.0398) were significantly associated with complications. Tumor volume greater than 14 cm3 was also significantly associated with subtotal resection (OR 8.3, p = 0.0201).Conclusions Resection of FMM carries perioperative morbidity that increases with larger tumor size. Despite the morbidity, long-term recurrence-free survival is achievable with maximal safe resection and adjuvant radiation.
Keywords: foramen magnum; meningioma; complications; outcomes; vertebral artery; surgical technique; approach; management